Rechtliche Aspekte der Einführung eines Emissionshandels-Systems für Treibhausgase in Deutschland und der EU - Sonja Butzengeiger (Hamburg Institute of International Economics (HWWA), 2001)
Die rechtliche Beurteilung von Emissionshandelssystemen (EHS) muss auf nationaler und gemeinschaftsweiter Ebene erfolgen. Bislang konnten die relevanten Aspekte auch von Experten nur allgemein diskutiert werden, da noch keine konkreten Regeln zur Ausgestaltung von Emissionshandelssystemen definiert wurden – weder auf nationaler noch auf internationaler Ebene. In der Fachliteratur wird eine große Anzahl rechtlicher Aspekte diskutiert. Werden diese Aspekte entsprechend ihrer Relevanz selektiert, so reduziert sich die Diskussion auf wenige Grundprobleme, deren Bedeutung jedoch nicht zu unterschätzen ist. – – Regardless the fact that the Kyoto Protocol of the UNFCCC has not been enforced internationally yet, many industrialised nations have already become active in setting up national climate programmes. Some states like the United Kingdom and Denmark are within the implementation process of national emissions trading regimes, others - like Australia, France, the Netherlands, Norway, New Zealand and also Germany - have started consultations on such systems. Some voices argue that emissions trading does not comply with legal requirements in Germany and therefore cannot be implemented. The purpose of this discussion paper is to review literature and expert discussions on the issue and to evaluate the thesis above. A juridical evaluation of a German emissions trading system must consider both national and European legislation. Many aspects can only be evaluated theoretically today. - If one reduces all aspects of ongoing discussions to the most critical ones, only a few but still important issues remain. These are: protection of property rights, confidence and stock; principle of legal equity; potential conflicts with the final constitution and finally coherence of emissions trading and voluntary commitments. The concrete design of an emissions trading scheme - e.g. allocation method chosen - will be crucial for its legality in Germany. A close co-operation between national authorities and industry seems advisable in order to minimise resistance and conflicts. Evaluating all legal aspects - some of which are discussed in a critical way by the experts - there seems to be no prohibitive barrier. It should be possible to design a national emissions trading system in Germany in a way that legal requirements are met.
Keywords: 330; Klimaschutz; Umweltzertifikat; Recht; Rechtsschutz; EU-Recht; Deutschland; EU-Staaten